A review of modern and conventional extraction techniques and their applications for extracting phytochemicals from plants - Chibuye Bitwell; Singh Sen Indra; Chimuka Luke; Maseka Kenneth Kakoma (Scientific African, 2023)
For centuries, phytochemicals have been of immense value to communities worldwide. These metabolites have been used in healthcare systems as medicines to treat various diseases. Further, phytochemicals are used as lead compounds in the synthesis of drugs. The extraction of compounds from plant materials is the cornerstone of natural product research. There has been a relentless endeavor to discover better extractive methods. In the same vein, several promising modern green extraction methods such as supercritical fluid, ultrasound, accelerated solvent, microwave, enzyme-assisted extraction methods are gaining significance. This review describes and discusses the various extraction techniques used to obtain the phytochemicals from different plant parts. These extraction techniques include the conventional solvent-based and the more robust modern and green extraction techniques. The review critically analyses the extraction conditions, optimized situations, advantages, and disadvantages of these extraction techniques. The review includes the recent applications of these extraction techniques. The review will propel advanced research and applications in the extraction process, a significant and integral component of natural products research.